Be prepared for livestock diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Manual on the Preparation of National Animal Disease Emergency Preparedness Plans. FAO Animal Health Manuals, number 6. 1999. 96 pp. ISBN 925104290x US$ 22 E 23.15